The Annexin-A1 mimetic RTP-026 promotes acute cardioprotection through modulation of immune cell activation - Jianmin Chen; Silvia Oggero; Chiara Cecconello; Jesmond Dalli; Hedayatullah Hayat; Ahmad Hjiej Andaloussi; Samra Sanni; Thomas EN Jonassen; Mauro Perretti (Pharmacological Research, 2023)
Aims: The cardio-protective and immuno-regulatory properties of RTP-026, a synthetic peptide that spans the Annexin-A1 (AnxA1) N-terminal region, were tested in rat acute myocardial infarction. Methods and results: In vitro, selective activation of formyl-peptide receptor type 2 (FPR2) by RTP-026 occurred with apparent EC50 in the 10–30 nM range. With human primary cells, RTP-026 counteracted extension of neutrophil life-span and augmented phagocytosis of fluorescent E.coli by blood myeloid cells. An in vivo model of rat acute infarction was used to quantify tissue injury and phenotype immune cells in myocardium and blood. The rat left anterior descending coronary artery was occluded and then reopened for 2-hour or 24-hour reperfusion. For the 2-hour reperfusion protocol, RTP-026 (25–500 µg/kg; given i.v. at the start of reperfusion) significantly reduced infarct size by ∼50 %, with maximal efficacy at 50 µg/kg. Analyses of cardiac immune cells showed that RTP-026 reduced neutrophil and classical monocyte recruitment to the damaged heart. In the blood, RTP-026 (50 µg/kg) attenuated activation of neutrophils and monocytes monitored through CD62L and CD54 expression. Modulation of vascular inflammation by RTP-026 was demonstrated by reduction in plasma levels of mediators like TNF-α, IL-1β, KC, PGE2 and PGF2α⊡ For the 24-hour reperfusion protocol, RTP-026 (30 µg/kg given i.v. at 0, 3 and 6 h reperfusion) reduced necrotic myocardium by ∼40 %. Conclusions: RTP-026 modulate immune cell responses and decreases infarct size of the heart in preclinical settings. Tempering over-exuberant immune cell activation by RTP-026 is a suitable approach to translate the biology of AnxA1 for therapeutic purposes.